Corpus architecturae religiosae europeae (IV-X saec.) - Introduction - Brogiolo, Gianpietro (Array, 2012)
The authors deliver a short history of the project Corpus Architecturae religiosae Europeae (IV-X saec.), begun in 2001: the corpus aims to catalogue the religios buildings of Europe between the 4th and the very beginning of the 11th c. The first results are reported, such as the chronological framework, the catalogue form, and the structure of the volumes.